Fully integrated wearable sensor arrays for multiplexed in situ perspiration analysis - Gao, Wei; Emaminejad, Sam; Nyein, Hnin Yin Yin; Challa, Samyuktha; Chen, Kevin; Peck, Austin; Fahad, Hossain M.; Ota, Hiroki; Shiraki, Hiroshi; Kiriya, Daisuke; Lien, Der-Hsien; Brooks, George A.; et al. (Nature (London), 2016)
By merging plastic-based skin sensors with silicon integrated circuits, a flexible, wearable perspiration analysis system is presented that measures skin temperature and the metabolites and electrolytes in human sweat and analyses the information in situ . A wearable plastic sweat biosensor Human sweat is attracting attention as a carrier of biomarkers of potential diagnostic importance, as well as in drug abuse detection and athletic performance optimization. In particular, sweat is much more tractable than other body fluids for continuous bio-monitoring. This paper presents a fully integrated flexible sensor platform for sweat analysis, based on existing technologies. Ali Javey and colleagues successfully connect plastic-based skin sensors to conventional silicon integrated circuitry to achieve multiple simultaneous measurement of sweat metabolites (glucose and lactate) and electrolytes (sodium and potassium). Skin temperature was measured to provide in situ calibration of the sensors. A small cohort human subject validation was performed to demonstrate the practical value of the platform — and a specially designed Android app created — for real-time assessment of physiological status, either as a wristband or forehead patch. Wearable sensor technologies are essential to the realization of personalized medicine through continuously monitoring an individual’s state of health 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 . Sampling human sweat, which is rich in physiological information 13 , could enable non-invasive monitoring. Previously reported sweat-based and other non-invasive biosensors either can only monitor a single analyte at a time or lack on-site signal processing circuitry and sensor calibration mechanisms for accurate analysis of the physiological state 14 , 15 , 16 , 17 , 18 . Given the complexity of sweat secretion, simultaneous and multiplexed screening of target biomarkers is critical and requires full system integration to ensure the accuracy of measurements. Here we present a mechanically flexible and fully integrated (that is, no external analysis is needed) sensor array for multiplexed in situ perspiration analysis, which simultaneously and selectively measures sweat metabolites (such as glucose and lactate) and electrolytes (such as sodium and potassium ions), as well as the skin temperature (to calibrate the response of the sensors). Our work bridges the technological gap between signal transduction, conditioning (amplification and filtering), processing and wireless transmission in wearable biosensors by merging plastic-based sensors that interface with the skin with silicon integrated circuits consolidated on a flexible circuit board for complex signal processing. This application could not have been realized using either of these technologies alone owing to their respective inherent limitations. The wearable system is used to measure the detailed sweat profile of human subjects engaged in prolonged indoor and outdoor physical activities, and to make a real-time assessment of the physiological state of the subjects. This platform enables a wide range of personalized diagnostic and physiological monitoring applications.